PENGARUH WORK–FAMILY CONFLICT, KEADILAN PROSEDURAL DAN BEBAN KERJA TERHADAP KEPUASAN KERJA PEGAWAI - Rendi Angger Pratopo; Suprayitno Suprayitno; Lamidi Lamidi (Universitas Slamet Riyadi, 2020)
The purpose of this research is to: 1) Analyze the significance effect of work family conflict on employee work satisfaction 2) Analyze the significance effect of procedural justice on employee work satisfaction 3) Analyze the significance effect of workload on employee work satisfaction This research is a survey research on employees of Regional Public Companies Surakarta City's Toya Wening Drinking Water. The study population was 174 people. The research sample of 88 employees with proportional cluster random sampling technique. Data collection techniques used a questionnaire. Data analysis techniques used multiple linear regression analysis, t test, test the accuracy of the model and the coefficient of determination. The results showed that worik family conflict has a negative and significant effect on employees work satisfaction. Procedural justice has a positive and significant effect on employees work satisfaction. Workload has a negative and significant effect on employees work satisfaction.